PENGARUH METODE QUANTUM LEARNING YANG DIPADU DENGAN MIND MAP TERHADAP HASIL BELAJAR - Subiyono Subiyono (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
This study aims at describing the influence of Quan-tum learning combined with Mind Map towards the outcome of Islamic education. This study is queasy-experiment with pretest-posttest design, learning outcome by written test, and questionnaire. The data are analyzed by inferential statistic: covariate and per-centage. The result shows that (1) there is no interactional influence between teaching model and pretest. (2) There is a significant influence of Quantum Learning method combined with Mind Map towards the achievement of Islamic Education. (3) Students have positive perception of the Quantum Learning combined with Mind Map in teaching Islamic Education, as it develops conducive learning condition.